Фінансова система в контексті формування та реалізації державної фінансової політики України - Трусова, Наталя Вікторівна; Трусова, Наталья Викторовна; Trusova, Natalia (My University, 2016)
UK: Розглянуто фінансову систему як фактор інтеграції сукупних елементів економічної системи держави. Обґрунтовано, що альтернативна модель формування та реалізації фінансової політики держави в контексті розвитку фінансової системи та дії економічних чинників забезпечує оптимальний розподіл вартості фінансових ресурсів між підприємствами, домогосподарствами, галузями, регіонами та фінансовими посередниками. Визначено механізм функціонування фінансової системи при розробці, плануванні та регулюванні державної фінансової політики. EN: The financial system as a factor of integration of elements of total economic system of the state has been considered. Financial system meets the interests of all actors, maintaining the proper level its structural and dynamic parameters to carry out its functions on the integration of the economy. Proved, that an alternative model of de-velopment and implementation of financial policy in the context of the financial system and of the economic factors provides optimum cost distribution of financial resources between businesses, households, industries, regions, and financial intermediaries. The mechanism of the financial system in the design, planning and regulation of the state financial policy has been determined. The substantial part of financial policy and its relationship with the norms of financial law, elements of the fi-nancial system and the financial mechanism for implementation of the concept of economic development of the state have been identify. The main the kinds of financial policy, that are considered to be fiscal policy, monetary policy and debt management, have been considered. Proved that fiscal policy is an integral financial policy in the field of taxation, government spending and the state budget to promote employment and curb inflation. The main tools of monetary poli-cy are the open market operations and the discount rate management. The policy of debt management is considering steps for preparation, issuance, placement of state debt, guarantees, maintenance and debt repayment.
Financial system in the context of forming and implementation of state and financial policy of Ukraine
Keywords: фінансова система; суб’єкти фінансової системи; державна фінансова політика; бюджетно-податкова політика; управління державним боргом; financial system; financial system entities; public financial policy; fiscal policy; public debt management